Sustainability Of Small And Medium Budget Hotel Operators In The East Coast Of Peninsular Malaysia - Sukarno, Siti Zaleha Mohd (2010)
Tourism is a significant industry in Malaysia. Small and medium budget hotel (SMBH) operators play a significant role to support the success of the tourism industry. This thesis explores the sustainability aspects of SMBH operators of the three states in the East Coast of Peninsular Malaysia. Among the factors explored were the owners/managers demographic profiles, their entrepreneurship characteristics and internal and external management factors influencing their business performance. Data were collected using the multi-methods approach, comprising questionnaire survey and face-to-face interview. A total of 48 SMBH operators were involved in the survey and only six respondents agreed to be interviewed. The localities of the research covered the three major urban centres in the East Coast of Peninsular Malaysia, namely Kota Bharu, Kuala Terengganu and Kuantan. The results show that majority of the owners/managers of the budget hotels were male, married and Malays, and they used their own resources to start and build up their businesses.